The syntactic features and emotional impact of Xitsonga interjections. - Mlambo, Respect; Hlungwani, Madala C. (Literator, 2024)
The syntactic features and emotional impacts of interjections in Xitsonga have been largely overlooked in existing literature. This article aims to close this gap by exploring these aspects. Employing a qualitative approach, the data were collected through corpus-based methods by extracting relevant words, phrases and sentences featuring interjections from published Xitsonga drama texts. The data were purposefully sampled and subsequently subjected to content analysis. The article was written following the principles of prototype theory. The findings revealed that Xitsonga interjections can occur at the beginning, middle and end of a sentence or occupy various positions within a sentence, and they are used to convey the speaker's emotional state, such as surprise, distress, fear, remembrance, frustration or anger. The article also notes that interjections can function as standalone utterances (holophrases) or adjuncts, enhancing emotional expression while maintaining grammatical integrity. Their placement significantly influences the emotions conveyed. The article further illustrates how juxtaposing interjections can heighten emotional intensity, showcasing their versatility in expressing complex emotional states. This applies to both primary and secondary interjections in Xitsonga. These findings suggest that interjections are an integral part of the Xitsonga, serving important syntactic features and expressing a range of emotional states. Contribution: This article enhances our understanding of Xitsonga by exploring the diverse syntactic features and emotional effects of interjections, an area that has received little attention. Drawing on data from published Xitsonga drama texts, the article reveals that interjections can appear at the beginning, middle or end of a sentence or occupy various positions, each carrying different emotional impacts. Using prototype theory as a framework, the article demonstrates that interjections function as standalone utterances (holophrases) or adjuncts, encompassing both primary and secondary forms. These insights deepen our understanding of Xitsonga's interjections, closing a research gap and contributing valuable knowledge to the fields of syntax and semantics.